La paradoja: crecimiento y desarrollo economico en el Perú (2001 – 2010) - Orozco Livia, Víctor (2011)
A paradox is a contradiction which according Ferrater Mora in his Dictionary of Fhilosophy Short, etymologically be interpreted as contrary to received opinion and common. In the case of the subject of this work would be the opinión released by the authorities responsible for economic policy in Peru, but which in fact is contrary or paradoxical to what is stated. In the Philosophical Dictionary Iudin Rosental and adds that a paradox arises the problem of finding the source of such annoyance and procedures to eliminate it. Therefore, the paper titled “The Paradox: Growth and Economic Development in Peru”, means knowing first what are the causes of this economic contraction, then a second time propose economic measures that tend to resolve it. The causes that lead to economic paradox in Peru are varied, covering economic, social, political, technological, philosophical, epistemological, ideological, etc., which certainly will not be fully addressed in this work, but if be assumed when the occasion demands.